Concentrations of LSD, 2-oxo-3-hydroxy-LSD, and iso-LSD in hair segments of 18 drug abusers. (March 2023) - Zheng, Jiaming; Wang, Xin; Zhang, Jiali; Ren, Hang; Zhao, Yunli; Xiang, Ping
Abstract: Lysergic acid diethylamide (LSD) is one of the most widely abused hallucinogens, which can alter consciousness, produce mental disorder, and cause harmful behavior. 1-Propionyl-LSD (1 P-LSD), a novel derivative of LSD, has the similar hallucinogenic effect. It is a control substance in several countries. 1 P-LSD can act as a prodrug for LSD and is rapidly hydrolyzed to LSD in humans. Therefore, LSD use should be confirmed by the absence of 1 P-LSD and in the detection of LSD. Here, we describe a LC–MS/MS method for the simultaneous extraction of LSD, iso-LSD, 2-oxo-3-hydroxy-LSD, and 1 P-LSD from hair. Hair samples (25 mg) were pulverized by cryogenic grinding in methanol. The limits of detection were 0.2–1 pg/mg and the limits of quantification were 0.5–2 pg/mg. This method was validated and applied to hair samples from 18 suspects who may have used LSD. Segmental hair analysis revealed a decrease in the LSD concentrations from the proximal to the distill end, while 1 P-LSD was not detected in any hair segments. The interpretation of hair analysis results of LSD still remains difficult. Nevertheless, concentrations of LSD and iso-LSD in human hair from 18 LSD users were reported. LSD concentrations were from <LOQ to 4.0 pg/mg ( n = 18, median 1.5 pg/mg) in the proximal 0–3 cm segment, from <LOQ to 1.8 pg/mg ( n = 8) in the 3–6 cm segment, and from <LOQ to 0.6 pg/mg ( n = 4) in the 6–9 cm segment. Iso-LSD ranged from <LOQ to 1.4 pg/mg ( n = 4) in the 0–3 cm segment and was detectable only in one 3–6 cm segment. To our knowledge, this is the first study to monitor LSD together with 1 P-LSD in hair. Graphical Abstract: ga1 Highlights: Method provides determination of LSD, iso-LSD, 2-oxo-3-hydroxy-LSD, and 1 P-LSD in hair. LSD concentrations reported in hair from 18 LSD users. Low hair concentrations of LSD (up to 4 pg/mg) detected in LSD users.